The Telegram notification system for improving library services Universitas Negeri Semarang - Kholiq Budiman; Mahargjo Hapsoro Adi; Akhmad Munawar; Aji Purwinarko (Jurnal Kajian Informasi dan Perpustakaan, 2022)
The pandemic period limits every activity, including library services, causing the communication distance between users and librarians to widen. Users often forgetting to return books, so the fines accumulated, and often forget and lose borrowed books. The communication distance between librarians and library users can be narrowed through an automatic reminder system to remind users of important information regarding fines, services, and others. This study aimed to know the Telegram notification system for improving library services. Universitas Negeri Semarang also supports the use of Telegram as a notification system. This study applied the Research and Development (RnD) method in The Senayan Library Management System (SLiMS) development, supported by an integration method using Middleware Integration. The use of the paired t-test in this study showed that this reminder mechanism successfully informed library members of the time limit for borrowing books and late fees. A significant relationship exists between before and after the installation of Telegram as a useful reminder system to avoid the accumulation of fines by customers. This reminder system was also beneficial to avoid users accumulating fines, it can be seen that the number of users who are late in returning books is decreasing as the notification system is implemented. Good communication between librarians and customers through an information system intermediary improves user service.